Effect of the gate metal work function on water-gated ZnO thin-film transistor performance. (1st June 2016) - Singh, Mandeep; Mulla, Mohammad Yusuf; Santacroce, Maria Vittoria; Magliulo, Maria; Di Franco, Cinzia; Manoli, Kyriaki; Altamura, Davide; Giannini, Cinzia; Cioffi, Nicola; Palazzo, Gerardo; Scamarcio, Gaetano; Torsi, Luisa
Abstract: ZnO thin films, prepared using a printing-compatible sol–gel method involving a thermal treatment below 400 °C, are proposed as active layers in water-gated thin-film transistors (WG-TFTs). The thin-film structure and surface morphology reveal the presence of contiguous ZnO crystalline (hexagonal wurtzite) with isotropic nano-grains as large as 10 nm characterized by a preferential orientation along the a -axis. The TFT devices are gated through a droplet of deionized water by means of electrodes characterized by different work functions. The high capacitance of the electrolyte allowed operation below 0.5 V. While the Ni, Pd, Au and Pt gate electrodes are electrochemically stable in the inspected potential range, electrochemical activity is revealed for the W one. Such an occurrence leads to an increase of capacitance (and current), which is ascribed to a high output current from the dissolution of a lower capacitance W-oxide layer. The environmental stability of the ZnO WG-TFTs is quite good over a period of five months.